2007
DOI: 10.1111/j.1872-034x.2007.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CYP3A aggravates endotoxin‐induced liver injury in hypophysectomized female rats

Abstract: Overexpression of CYP3A aggravated LPS-induced liver injury in rats, apparently through the formation of reactive oxygen species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…Cyclooxygenase 2 is also expressed by the endometrial tissues and cells, and PGE 2 or a cAMP analogue has been shown to induce StAR and aromatase expression and activity in the endometriotic stromal cells 5. We also found an elevated expression of CYP19A1, StAR, and COX-2 in EC as compared to EU and EN; however, their expression in EN compared to EU contrasted from previously reported studies 5,8,10,11,18,47,48. The most likely explanation for the difference could be the method of detection and primers used in these as compared to our study 48.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Cyclooxygenase 2 is also expressed by the endometrial tissues and cells, and PGE 2 or a cAMP analogue has been shown to induce StAR and aromatase expression and activity in the endometriotic stromal cells 5. We also found an elevated expression of CYP19A1, StAR, and COX-2 in EC as compared to EU and EN; however, their expression in EN compared to EU contrasted from previously reported studies 5,8,10,11,18,47,48. The most likely explanation for the difference could be the method of detection and primers used in these as compared to our study 48.…”
Section: Discussioncontrasting
confidence: 70%
“…Aromatase is expressed in a number of cells and tissues, and in the endometrium it is expressed by the stromal cells with elevated expression in EC endometrium. 5,[8][9][10] The expression of CYP19A1 in endometrial stromal cells (ESCs) is regulated by StAR, which has a rate-limiting regulatory function on steroid production in a number of cell types. 7,11 The expression of StAR is regulated by many factors, including luteinizing hormone (LH) receptor-activation of cyclic adenosine monophosphate (cAMP) and several cytokines and growth factors that are expressed by the endometriotic tissues.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…This dosage of LPS was used in our previous studies 26 and by others. 27,28 At different time points (0, 2, 4, 8, and 12 h (n ¼ 7)), the animals were killed; blood and liver tissue were taken for analytical examination. All animals received humane care according to the criteria outlined in the 'Guide for the Care and Use of Laboratory Animals' prepared by the National Academy of Sciences and published by the National Institutes of Health (NIH publication 86-23 revised 1985).…”
Section: Materials and Methods Endotoxic Shockmentioning
confidence: 99%
“…These two receptors mediate the effects of xenobiotics and therapeutic drugs on the regulation of CYP3A [ 18 ]. Sequence analysis showed that PXR and CAR are closely related to each other, and both require heterodimerization with RXR for high-affinity DNA binding [ 19 , 20 ], as shown in Figure 10 .…”
Section: Resultsmentioning
confidence: 99%